Investigating the Relationship between Psychological Capital and Physical Activity among University Students: The Mediating Effects of Health Consciousness and Health Motivation - Dan Huang; Hui Tang; Longjun Jing; Hanyue Lei; Xieji Li; Denise Koh (SAGE Open)
Physical inactivity among university students is a growing concern, significantly impacting their overall health and well-being. Understanding the factors that influence physical activity is essential for promoting healthier lifestyles in this demographic. Grounded in Self-Determination Theory and the Health Belief Model, this study investigates how psychological capital affects college students’ physical activity, focusing on the chain mediating roles of health consciousness and health motivation. Data were collected from a questionnaire survey of 1,103 college students across seven universities in the Chang-Zhu-Tan metropolitan area and analyzed using structural equation modeling with Smart-PLS. The results indicate that psychological capital significantly predicts health consciousness, health motivation, and physical activity, with both mediators forming a significant chain mediation pathway. These findings suggest that psychological capital can promote physical activity by enhancing students’ awareness of health risks and benefits (as conceptualized in the Health Belief Model) and fostering internalized motivation (as proposed by Self-Determination Theory). Based on this, universities should develop strategies to enhance students’ psychological resources, raise their health awareness, and cultivate intrinsic motivation for physical activity, thereby promoting healthier and more active lifestyles.